Determinants of green workplace behaviour in Malaysian public service organisations - Sabri, Mohamad Fazli; Razak, Norjumaaton Fazhani; Magli, Amirah Shazana; Mohd Yusoff, Ahmad Nasir; Wijekoon, Rusitha (Faculty of Human Ecology, Universiti Putra Malaysia, 2022)
To improve sustainability in the working environment, latest studies have concentrated on activities that stimulate employees’ green behaviour. Over the past decade, there had been a substantial increase in the number of studies conducted on individual’s green practices in the workplace. This study focused on organisational green behaviour as a new construct to identify determinants of green workplace behaviours (GWB) in the governmental work setting in Malaysia. This research applied the Theory of Planned Behaviour (TPB) as the study framework and data were gathered from 460 respondents from public organisations in Malaysia. According to the results, colleague, supervisor, perceived behavioural control (PBC), intention and knowledge showed a significant positive association as determinants of GWB, but only attitude was not significant. The study contributed to the body of knowledge and broadened the understanding of green human resource management (GHRM) in Malaysian public service organisations. Employers and organisations may benefit from adopting the study implications as a guide to inspire GWB in the workplace.